(untitled) (MAUSAM, 1996)
This article uses daily rainfall data (April-October) of Cooch Behar (1971-90) and Jalpaiguri (1972-90), the two predominantly rainfed farming districts of Terai zone of West Bengal, to study the, nature of different rainfall parameters of this area. It was observed that the mean date of Onset of Effective Monsoon (OEM) of this region is about one month in advance from the normal occurrence of monsoon over Kerala. However, the monsoon rains, here, retreat at about the same time with those of Kerala. Distribution of the duration of dry spell has been studied to have some idea of the nature of critical dry spells during the monsoon season. The article also examines how prolonged, on the average, are the monsoon breaks for different return periods. Expected length of dry spell (in days) for 2, 5, 10 and 20 years return periods have been estimated with the help of suitably fitted curves for each location.